Guía didáctica dirigida a estudiantes de octavo año de EGB basada en constructivismo para la educación patrimonial de la iglesia San Juan Bautista de Yaruquíes y su entorno - Verdesoto Parra, Yadira Estefanía (2025)
This research proposes a teaching guide with a constructivist approach to promote heritage education in eighth-grade students of Basic General Education, focusing on the San Juan Bautista Church of Yaruquíes and its cultural environment. It is based on the recognition of heritage as a set of tangible and intangible assets that reflect the identity and historical memory of a community, as identified through fieldwork and research. The church, built between 1950 and 1964, houses a valuable collection of sculptures, paintings, altarpieces, and metalwork dating back to the 18th century, many of them linked to Quito schools. It also identifies heritage elements not formally registered, such as religious brotherhoods and local symbolic spaces. Following a qualitative approach, the research conducted interviews that consolidated the historical memory of residents regarding the cultural significance of the church and its festivals, revealing a need to strengthen young people's connection to their cultural heritage. The designed teaching guide is aligned with the national curriculum and proposes activities based on the constructivist pedagogical model, fostering active learning, critical thinking, and heritage appropriation. This proposal seeks not only to inform but also to motivate students to value and preserve the cultural elements of their environment as part of their collective identity. Thus, heritage education is presented as a key tool for conserving the historical and cultural legacy of Yaruquíes